Employee Motivation and Job Performance of Non-Academic Staff in Chinese Universities - Ce, Zhang; Rossazana, Ab. Rahim; Fadilah, Siali; Nuradibah, Mokhtar (MDPI, 2025)
This study investigates the relationship between monetary and non-monetary motivations and financial and non-financial job performance among non-academic staff in Chinese universities. Using data from 356 respondents, analyzed via Structural Equation Modeling (SEM-PLS) with Smart-PLS4, this study finds that both incentive types significantly affect performance. Monetary incentives such as salaries and bonuses primarily enhance f inancial performance; on the contrary, non-monetary incentives such as training, career advancement, and supportive work environments have a stronger impact on nonfinancial performance, including job satisfaction and service quality. The findings underscore the importance of implementing balanced motivation strategies that integrate both financial rewards and developmental support. From a policy perspective, this study recommends customized incentive systems to improve administrative effectiveness and contribute to the strategic development of universities. These insights offer practical guidance for strengthening human resource practices and maximizing the performance of non-academic personnel in the context of higher education in China.